How far have we come? Artificial intelligence for chest radiograph interpretation. Issue 5 (May 2019) - Kallianos, K.; Mongan, J.; Antani, S.; Henry, T.; Taylor, A.; Abuya, J.; Kohli, M.
Abstract : Due to recent advances in artificial intelligence, there is renewed interest in automating interpretation of imaging tests. Chest radiographs are particularly interesting due to many factors: relatively inexpensive equipment, importance to public health, commonly performed throughout the world, and deceptively complex taking years to master. This article presents a brief introduction to artificial intelligence, reviews the progress to date in chest radiograph interpretation, and provides a snapshot of the available datasets and algorithms available to chest radiograph researchers. Finally, the limitations of artificial intelligence with respect to interpretation of imaging studies are discussed.